(untitled) (Swiss Medical Weekly, 2015)
Since 2010, awareness of the global threat caused by antimicrobial resistance (AMR) has risen considerably and multiple policy and research initiatives have been implemented. Research and development (R&D) of much-needed new antibiotics active against multiresistant pathogens is a key component of all programmes aiming at fighting AMR, but it has been lagging behind owing to scientific, regulatory and economic challenges. Although a few new antibiotics might be available in Switzerland in the next 5 years, these new agents are not based on new mechanisms of action and are not necessarily active against resistant pathogens for which there is the highest unmet medical need, i.e. multiresistant Gram-negative bacteria. Of the three new antibiotics with pending authorisation in Switzerland for systemic treatment of severe infections, oritavancin and tedizolid target Gram-positive pathogens, while only ceftolozane+tazobactam partially covers multiresistant Gram-negative pathogens. Among six antibiotics currently in phase III of clinical development, delafloxacin and solithromycin will also be useful mostly for Gram-positive infections. Importantly, the four other compounds are active against multiresistant Gram-negative pathogens: ceftazidime+avibactam, meropenem+RPX7009, eravacycline and plazomicin. The three last compounds are also active against carbapenem-resistant Enterobacteriaceae (CRE). A few compounds active against such pathogens are currently in earlier clinical development, but their number may decrease, considering the risk of failure over the course of clinical development. At last, through public and political awareness of pathogens with high public health impact and unmet medical need, development of innovative economic incentives and updated regulatory guidance, R&D of new antibiotics is slowly taking off again.